Brevibacillin 2V Exerts Its Bactericidal Activity via Binding to Lipid II and Permeabilizing Cellular Membranes - Zhao, Xinghong; Wang, Xiaoqi; Shukla, Rhythm; Kumar, Raj; Weingarth, Markus; Breukink, Eefjan; Kuipers, Oscar P. (Frontiers in Microbiology, 2021)
Lipo-tridecapeptides, a class of bacterial non-ribosomally produced peptides (NRPs), show strong antimicrobial activity against Gram-positive pathogens, including antibiotic-resistant Staphylococcus aureus and Enterococcus spp. However, many of these lipo-tridecapeptides have shown high hemolytic activity and cytotoxicity, which has limited their potential to be developed into antibiotics. Recently, we reported a novel antimicrobial lipo-tridecapeptide, brevibacillin 2V, which showed no hemolytic activity against human red blood cells at a high concentration of 128 mg/L, opposite to other brevibacillins and lipo-tridecapeptides. In addition, brevibacillin 2V showed much lower cytotoxicity than the other members of the brevibacillin family. In this study, we set out to elucidate the antimicrobial mode of action of brevibacillin 2V. The results show that brevibacillin 2V acts as bactericidal antimicrobial agent against Staphylococcus aureus (MRSA). Further studies show that brevibacillin 2V exerts its bactericidal activity by binding to the bacterial cell wall synthesis precursor Lipid II and permeabilizing the bacterial membrane. Combined solid-state NMR, circular dichroism, and isothermal titration calorimetry assays indicate that brevibacillin 2V binds to the GlcNAc-MurNAc moiety and/or the pentapeptide of Lipid II. This study provides an insight into the antimicrobial mode of action of brevibacillin 2V. As brevibacillin 2V is a novel and promising antibiotic candidate with low hemolytic activity and cytotoxicity, the here-elucidated mode of action will help further studies to develop it as an alternative antimicrobial agent.